Grupo grande de personas. (UNED, 2024)
Aparecen a la izquierda Emel Ramirez Corrales, Guillermo Vindas Gómez, Fernando Ureña Elizondo, Mario Bolaños Mora, Gisele Boñalos Mora, Carlos Quesada Carvajal, Jarol Arias Le Claire, Oliver Bach Weithaeuser, Carlos Rojas Quesada, sentadas en el mismo orden Lorena Quesada Arce, María Cascante Prada, Marlen Víquez Salazar, Nuria Rodríguez Sama, Flor Montero Arce, Amalia León Blanco, Ligia Garro Mora, Grettel Mena Araya